الرضـــا الـوظــــيفي و الكــــفاءة المــــهنية دراسة ميدانية شركة سوف للدقيق - الشط – الوادي انموذجا - خميدة مبروكة آية; علاق منار (جامعة الوادي - University of Eloued, 2025)
"تكتسي هذه الدراسة أهمية بالغة في سعيها الى ابراز الدور الذي يلعبه الرضا الوظيفي في تحسين الكفاءة المهنية مما يمكن المؤسسة من تحقيق اهدافها بكفاءة وفعالية ، كما تهدف الى التعرف على اهم العوامل المؤثرة في رضا العاملين وتحسين مستوى كفاءتهم الإنتاجية ، اعتمدت الدراسة على المنهج الوصفي باعتباره الأنسب لطبيعة الموضوع و تم استخدام الاستبيان كأداة رئيسية لجمع البيانات، وقد استخدمت الدراسة اسلوب المسح الشامل حيث شملت الدراسة جميع أفراد المجتمع الأصلي المتمثل في 35 عاملاً في شركة سوف للدقيق – الشط – بالوادي . وقد تم تأطير الدراسة نظريا من خلال نظرية الخصائص الوظيفية لـ هاكمان و أولدهم لمناقشة فروض الدراسة . وبعد جمع البيانات وتحليلها احصائياً تم التوصل الى عدد من النتائج و هي : • ان نسبة معتبرة من المبحوثين عبرو عن رضاهم النسبي عن اجورهم 43.8% و قد ترافق ذلك مع مستويات جيدة من الانتاجية مما يشير الى ان الاجر يعد احد العوامل المؤثرة في رفع الكفاءة المهنية و ان كانت تأثيرا متوسطا نسبيا مقارنة بعوامل أخرى. • أن اغلبية افراد الدراسة 46.9% يرون ان هناك تعاونا بين الأقسام وتواصلا بناء مع الإدارة ، مما يوفر جوا ً مهنيا يساعد على الاندماج و زيادة الشعور بالإنتماء و هو ما ينعكس ايجابا على مستوى الأداء و الكفاءة المهنية. • حيث اظهر نسبة عالية 75 %من المبحوثين تأكيدهم على أهمية نظام المكافآت خاصة فيما يتعلق بامكافآت المادية مما يعكس ارتباطا واضحا بين التحفيز و الرفع من الكفاءة المهنية . "This study is of great importance in its attempt to highlight the role that job satisfaction plays in improving professional competence, which enables the organization to achieve its objectives efficiently and effectively. It also aims to identify the most significat factors influencing employee. Satisfaction and enhancing their productity levels. The study adopted the descriptive approach as the most suitable method for the nature of the topic , and the questionnaire was used as the main tool for data collection. A Comprehensive survey method was applied , as the study included all members of the original population, consisting of 35 employees at SOUF Flour Company – El Shatt – El Oued The theoretical framework of the study was based on Hackman and Oldham’s Job Characteristics Theory to discuss the research hypotheses. After collecting and statistically analyzing the data , several findings were reached, including: A considerable proportion of the respondents expressed relative 43.8% satisfaction with their wages, which was accompanied by good levels of productivity. This indicates that salary is one of the factors influencing the improvement of professional competence, although its effect is relatively moderate compared to other factors. Most members of the sample 46.9% indicated that there is cooperation between departments and constructive communication with management, which creates a professional environment that promotes integration and strengthens the sense of belonging. This, in turn, positively affects performance and professional competence. A high percentage of the respondents 75% emphasized the importance of the incentive system, particularly regarding material rewards, which reflects a clear link between motivation and the enhancement of professional competence.
مذكرة ماستر قسم علوم الاجتماعية تخصص علم اجتماع تنظيم وعمل.
Keywords: المؤسسة الاقتصادية; الكــــفاءة المــــهنية; الرضـــا الـوظــــيفي; Job satisfaction; Professional competence; Economic institution